2021
DOI: 10.24083/apjhm.v16i4.813
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Employee Performance Appraisal System in Health Sector: Evidence from Iranian organizations

Abstract: Introduction: Performance appraisal is a formal process to review and improve the organizational performance of employees regularly. Despite the appropriate organizational frameworks for performance appraisal, they are not apparently addressing the operational realities of health care organizations. This study thus aimed to examine the effectiveness of the current performance appraisal system of employees at Tehran University of Medical Sciences (TUMS) from the perspective of employees. Methods: The data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Also, this may be attributed to work load, lack of time, lack of supervisors' communication skills, fear of upsetting colleagues, fear of damaging professional relationships, defensive behaviour and resistance of nurses when receiving feedback. This result was consistent with researches conducted by van Tjahjono et al (2020) , Majidi et al, (2021) , Homauni et al, (2021) and Mok and Yie, (2021) indicated that nurses perceived low level of performance appraisal fairness and performance feedback had the lowest average score and concluded that Health workers' performance appraisal is facing a number of challenges, including ineffectiveness of appraisal data for performance improvement, lack of immediate and constructive feedback and unfair performance appraisal.…”
Section: Fairness Performance Appraisalsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, this may be attributed to work load, lack of time, lack of supervisors' communication skills, fear of upsetting colleagues, fear of damaging professional relationships, defensive behaviour and resistance of nurses when receiving feedback. This result was consistent with researches conducted by van Tjahjono et al (2020) , Majidi et al, (2021) , Homauni et al, (2021) and Mok and Yie, (2021) indicated that nurses perceived low level of performance appraisal fairness and performance feedback had the lowest average score and concluded that Health workers' performance appraisal is facing a number of challenges, including ineffectiveness of appraisal data for performance improvement, lack of immediate and constructive feedback and unfair performance appraisal.…”
Section: Fairness Performance Appraisalsupporting
confidence: 90%
“…Motivation meets the needs of the staff, improve communication and interpersonal relationship between manger and nurse's, increase self-esteem and sense of belonging to organization, increase staff retention (Mohammad, Elliethey, Elzohairy, 2021). Motivated nurses have high levels of morale and commitment towards the organization and its goals and objectives, motivation reduces turnover and reduces the need for constant induction of new staff and help marketing of organization (Homauni et al, 2021). Researchers have suggested that nurses and supervisors hold negative views on the appraisal process and its degree of fairness.…”
Section: Significance Of the Studymentioning
confidence: 99%